2008
DOI: 10.1086/524691
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deficiency of Chemokine Receptor CCR5 Is a Strong Risk Factor for Symptomatic West Nile Virus Infection: A Meta‐Analysis of 4 Cohorts in the US Epidemic

Abstract: West Nile virus (WNV) causes disease in approximately 20% of infected humans. We previously reported that homozygosity for CCR5Delta32, a nonfunctional variant of chemokine receptor CCR5, is markedly increased among symptomatic WNV-seropositive patients from Arizona and Colorado. To confirm this, we analyzed cohorts from California and Illinois. An increase in CCR5-deficient subjects was found in both (for California, odds ratio [OR], 4.2 [95% confidence interval {CI}, 1.5-11.9] [P= .004]; for Illinois, OR, 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 15 publications
4
133
1
4
Order By: Relevance
“…These studies have analyzed the complete loss-of-function allele, CCR5D32, among WNV-infected cohorts. In our initial studies, a strong association between CCR5D32 homozygosity (CCR5-deficient individuals) and symptomatic WNV disease was reported [26,27,40]. Compared to a reference cohort of uninfected random blood donors, where the frequency of CCR5D32 homozygosity was *1 %, the frequency among WNVinfected individuals with symptomatic disease (meningitis, encephalitis) was highly enriched (*4-5 %; p \ 0.0001).…”
Section: Ccr5mentioning
confidence: 90%
See 1 more Smart Citation
“…These studies have analyzed the complete loss-of-function allele, CCR5D32, among WNV-infected cohorts. In our initial studies, a strong association between CCR5D32 homozygosity (CCR5-deficient individuals) and symptomatic WNV disease was reported [26,27,40]. Compared to a reference cohort of uninfected random blood donors, where the frequency of CCR5D32 homozygosity was *1 %, the frequency among WNVinfected individuals with symptomatic disease (meningitis, encephalitis) was highly enriched (*4-5 %; p \ 0.0001).…”
Section: Ccr5mentioning
confidence: 90%
“…Several epidemiologic studies have been conducted to evaluate the role of CCR5 in controlling WNV infection in humans as well [26,27,[38][39][40]. These studies have analyzed the complete loss-of-function allele, CCR5D32, among WNV-infected cohorts.…”
Section: Ccr5mentioning
confidence: 99%
“…More than 29,000 human cases have been diagnosed with severe WNV infection in the continental United States during the past decade, and many more have been infected and remain undiagnosed. Advanced age is by far the greatest risk factor for severe neurological disease, long-term morbidity, and death (2), although a genetic basis of susceptibility also has been recently identified (3,4).…”
mentioning
confidence: 99%
“…Corroborating the results of previous studies in mice (reviewed in [67]), studies in humans have shown that CCR5∆32 heterozygotes have a sixfold increased risk for severe West Nile virus (WNV) infection and a five-fold increased risk of mortality [68]. A meta-analysis of the four patient cohorts in the United States confirmed that CCR5 deficiency is a strong and consistent risk factor for symptomatic WNV infection [69]. An additional association between the lack of functional CCR5 due to the CCR5∆32 deletion and tick-borne encephalitis has also been reported [70].…”
Section: The Development Of Ccr5 Inhibitors As Anti-hiv Therapeutics mentioning
confidence: 69%